On the Main Methodological Problems of a Critical Theory of Anti-Semitism: Adorno’s Contribution and Its Later Elaboration - Nový, Martin (Dějiny – teorie – kritika, 2016)
This contribution analyses Adorno’s conceptualisation of anti-Semitism, discussing first the general method of explaining modern social phenomena within a critical theory, in order to then focus on the particular way in which Adorno relates particular social phenomena to the universal capitalist foundation. On this basis, Adorno then interprets the relation between the social and the psychological dimensions of anti-Semitism, showing that on a conscious level, anti-Semitic ideology is based on an erroneous understanding of the internal relation between production, circulation, and consumption. The mistaken notion that exploitation takes place on the level of circulation is an illusion which reflects the way in which capitalist society prima facie appears. Postone and Bonefeld, who further develop Adorno’s thoughts, build on the distinction between the phenomenal form and the essence of particular historical social relations. According to contemporary critical theoreticians, anti-Semitism is an irrational form of anti-capitalism which fails to grasp the internal link between the abstract and the concrete aspect of capitalism. The contribution of this study for historiographic methods is twofold: it shows how the critical theory offers ways of interpreting phenomena related to anti- Semitism and it adds its modest share to the methodology of conceptualisation of social phenomena in the capitalist era.